Optimalisasi Program Pengelolaan Sampah Melalui Inovasi “Pilah Sampah Dapat Emas” di Kampung Yosoroto Kota Surakarta - Ratna Puji Lestari; Ghufronudin .Ghufronudin; Danang Purwanto (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
Rubbish that piles up aroud the residence can cause an unpleasant odor that makes residents uncomfortable including residents of Yosoroto Village, Surakarta. Research conducted at the Kitiran Emas waste bank in Yosoroto Village aims todescribe the gade clean and gold program carried out at the waste bank. Researches focused on the study of the management’s efforts to optimize the gade clean and gold program. Research was conducted using qualitative methods through a case study approach. Research data were collected through in-depth interviews, observation, and documentation. The infromants in this study were waste bank menager, head of neighborhood and pawnshops who were selected using a purposive sampling technique. To test the validity of the data is done by triangulation of sources and data analysis is done using Miles and Haberman analysis techniques. Based on the researches, it can be concluded that the gade clean and gold programas an innovation in waste management in Yosoroto Village can be accepted by the community. The program provides benefits to the community because it easy to understand and in line wth community knowledge. Various communication channels are alseo used to socialize the program. The implememntation of the program requires time, which starts from the program is launched until it is finally implemented by the community. The existence of this program the forms a new mindset and lifestyle in the community to managing waste.